2020
DOI: 10.1016/j.jbusres.2019.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder integration, environmental sustainability orientation and financial performance

Abstract: Despite the growing research on the influence of stakeholder integration on organizational outcomes, our understanding of the specific firm-level conditions that may mediate the relationship between stakeholder integration and financial performance is lacking. Using primary data gathered from 233 small and medium-sized enterprises in Ghana, we found empirical support for our contention that the link between stakeholder integration and financial performance is mediated by a firm's environmental sustainability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(121 citation statements)
references
References 142 publications
3
88
1
4
Order By: Relevance
“…This is our attempt to address the lack of sector-specific analysis in the literature with regard to how such firms' policies evolve to respond to uncertainty and pressures in their environment (Fuchs & Mazmanian, 1998). Our findings also lend support to the thesis that SPs are shaped by a quest to achieve sustainable competitive advantage (Amankwah-Amoah, Amankwah-Amoah, Bansal & Roth, 2000;Danso, Adomako, Lartey, et al, 2019).…”
Section: Theoretical and Practical Implicationssupporting
confidence: 60%
“…This is our attempt to address the lack of sector-specific analysis in the literature with regard to how such firms' policies evolve to respond to uncertainty and pressures in their environment (Fuchs & Mazmanian, 1998). Our findings also lend support to the thesis that SPs are shaped by a quest to achieve sustainable competitive advantage (Amankwah-Amoah, Amankwah-Amoah, Bansal & Roth, 2000;Danso, Adomako, Lartey, et al, 2019).…”
Section: Theoretical and Practical Implicationssupporting
confidence: 60%
“…Empirical results also support that the strength of the relationship between strategic orientation dimensions and performance may vary depending on both external and internal factors [44]. External factors that have been examined include the competitive intensity, market turbulence, and technological change [16,41], and internal factors include top management profiles and competitive strategies [45]. While these studies provide evidence that both external and internal factors play important roles in moderating the orientation-performance relationship, most extant research on strategic orientations has been conducted in Western countries.…”
Section: The Contextual Mechanism On Strategic Orientationsmentioning
confidence: 69%
“…Then, extended from the RBV, the natural resource-based view [39] suggested that firms that integrate environmental constraints into organizational processes will be enabled to acquire valuable, rare, and inimitable new resources, constituting the basis of firm's long-term competitive advantage [40]. Additionally, given the legitimacy issue, firms driven by a sustainability orientation will develop and design products more for the sustainability of global systems [41], which help them facilitate better reputation and greater legitimacy, consequently increasing the accessibility to greater market share and revenues [42]. Based on the above analysis, we propose that: Hypothesis 2 (H2).…”
Section: Sustainability Orientation and Firm Growthmentioning
confidence: 99%
“…More recent research has shown that there is a positive relationship between the investment and the successful deployment of CSR, positively affecting the level of satisfaction of employees and customers, and the profitability of investments [71,72]. More recent studies in the field of SMEs on CSR practices indicate that to meet the needs of stakeholders these types of companies are adopting global practices, such as environmental actions, ecological products, marketing-focused campaigns, and social and green marketing-innovation, in the organizational climate (based on guidelines from international organizations) [73,74]. These strategies are leading them to compete with larger corporations and moving them towards achieving significant organizational and financial results [75,76].…”
Section: The Relationship Of Csr With Financial Performancementioning
confidence: 99%